2012
DOI: 10.1002/ps.3438
|View full text |Cite
|
Sign up to set email alerts
|

The repelling effect of plant secondary metabolites on water voles, Arvicola amphibius

Abstract: The identification of an effective water vole repellent could help to reduce damage to crops. It may also minimise the use of kill traps and of rodenticides, which will be of benefit for non-target organisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Microorganisms are known to play a key role in soil quality and health. In this way, the microbial biomass as well as the enzymatic activity are potential indicators of soil quality, since they are directly Cymbopogon nardus Antagonist of octopamine Dayan et al (2009) and Fischer et al (2013) correlated with the soil biology and for rapidly responding to changes due to anthropogenic and environmental action. Stimulating or inhibitory effects may be observed after the application of essential oils and/or their compounds alone, in microorganisms (Stamou et al, 2017;Vokou, 2007) and soil enzymes (Papatheodorou et al, 2014;Stamou et al, 2017).…”
Section: Botanical Pesticides: Randd Gaps and Marketmentioning
confidence: 99%
“…Microorganisms are known to play a key role in soil quality and health. In this way, the microbial biomass as well as the enzymatic activity are potential indicators of soil quality, since they are directly Cymbopogon nardus Antagonist of octopamine Dayan et al (2009) and Fischer et al (2013) correlated with the soil biology and for rapidly responding to changes due to anthropogenic and environmental action. Stimulating or inhibitory effects may be observed after the application of essential oils and/or their compounds alone, in microorganisms (Stamou et al, 2017;Vokou, 2007) and soil enzymes (Papatheodorou et al, 2014;Stamou et al, 2017).…”
Section: Botanical Pesticides: Randd Gaps and Marketmentioning
confidence: 99%
“…For example, Pelz (1989) has shown that wood mice [Apodemus sylvaticus (Linnaeus, 1758)] can be lured away from sugar beet seeds by providing an attractive alternative food adjacent to the newly planted crop and concentrated volatiles may drive rodents away from fields or other structures (e.g. Curtis et al 2002;Fischer et al 2013aFischer et al , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Scotch broom is known to be an allelopathic shrub that produces a set of different alkaloid compounds (Gresser et al, 1996;Grove et al, 2012). Further analyses should be conducted to investigate whether these shrubs can effectively alter the feeding behavior of rodents, as has already been shown for other plants (Curtis et al, 2002;Fischer et al, 2013;Hansen et al, 2016).…”
Section: Discussionmentioning
confidence: 97%